First-Principles Study of Molecular Adsorption of Hydrogen/s on Co-Adatom Graphene - Pantha, Nurapati; Thapa, Saroj; Adhikari, Narayan Prasad (Journal of Institute of Science and Technology, 2020)
The study of graphene and its allotropes help to understand fundamental science and their role in the industry. The adsorption of transition metal adatom on mono-layer graphene can tune the geometrical, electronic, and magnetic properties of the material according to the requirement for the practical applications. In the present work, the geometrical stability, electronic and magnetic properties, and also the redistribution of electronic charge of single cobalt atom (Co) adsorbed graphene with reference to pure graphene have been investigated to develop a model system for the effective storage of hydrogen. The density functional theory (DFT) based first-principles calculations by incorporating van der Waals (VDW) interactions within DFT-D2 levels of approximation implemented in the quantum ESPRESSO package was used. The band structure and density of states of cobalt-adatom graphene show that the material is metallic and magnetic with a total magnetic moment of 1.55 μB. The change in the electronic distribution of Co-adatom graphene has been found favorable for adsorbing molecular hydrogen/s with greater strength. The increasing number of adsorbed molecular hydrogen/s (n=1 to 7) onto the substrate shows varying binding energy per hydrogen molecule, high enough at low concentration (n=1, 2, and 3), and then decreases slowly on increasing the value of n. The nature of adsorption and binding energy per hydrogen molecule (with a range of 0.116 - 0.731 eV/ H2) are found useful to meet a standard target for hydrogen storage in such materials.